2015
DOI: 10.1007/s00221-015-4225-9
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the SNARC effect: distance–number mapping occurs in the peripersonal space

Abstract: Estimating distance of objects relative to one's body is important for interaction with the environment. Given that distance is an interval of magnitude describing space, distance and the commonly used estimations of magnitude, i.e., numbers, may share a common representation system (the ATOM theory, Walsh in Trends Cogn Sci 7(11):483-488, 2003). The current study systematically examined the association between distance and number representations on both the sagittal and transverse axes on the transverse plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…As in Experiment 1, the correlation between implicit-DE and explicit-DE was not significant. As hypothesized, the SNARC effect driven by the numerical magnitude was modulated by the diagonal response mappings: Only the diagonal congruent with the MNL (i.e., from leftclose to right-far) led to negative and significant regression slopes, indicating an association of small/large numbers with left-close and right-far space (Aleotti et al, 2022;Chen et al, 2015;Gevers, Lammertyn et al, 2006; confirmed by the Bayesian analyses, see Appendix B). Conversely, the diagonal incongruent with the MNL (i.e., from left-far to right-close) led to positive and significant regression slopes (the Bayesian analyses reported inconclusive evidence, see Appendix B).…”
Section: Discussionsupporting
confidence: 60%
“…As in Experiment 1, the correlation between implicit-DE and explicit-DE was not significant. As hypothesized, the SNARC effect driven by the numerical magnitude was modulated by the diagonal response mappings: Only the diagonal congruent with the MNL (i.e., from leftclose to right-far) led to negative and significant regression slopes, indicating an association of small/large numbers with left-close and right-far space (Aleotti et al, 2022;Chen et al, 2015;Gevers, Lammertyn et al, 2006; confirmed by the Bayesian analyses, see Appendix B). Conversely, the diagonal incongruent with the MNL (i.e., from left-far to right-close) led to positive and significant regression slopes (the Bayesian analyses reported inconclusive evidence, see Appendix B).…”
Section: Discussionsupporting
confidence: 60%
“…The vertical SNA could be based on gravity and more broadly on the natural laws according to which "More is Up -Less is down" (Lakoff & Johnson, 2008). While experimental studies regarding the sagittal axis are scarce, SNAs related to depth (near vs. far) could emerge in the peripersonal space (Chen et al, 2015). We posit that processing the spatial distance between an object/stimulus and usmore space, larger magnitude, and vice-versacould be a reliable hypothesis for accounting for the SNAs observed across vertical and sagittal axes.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating SNAs along this axis is of critical interest given the scarcely available literature about it. For instance, Chen et al (2015) conducted a SNARC-like experiment to understand SNAs in a peripersonal space in which the response buttons were organized as near and far, and they found a reliable effect in performance favoring responses of the sort small/near versus large/far. Nevertheless, this axis is thought to share many mechanisms with the vertical axis, and in fact, the vertical and midsagittal axes are often interchanged with one another in the literature (Ito & Hatta, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We used saccadic responses because they allow to separate the responses along the true horizontal and vertical spatial axes by placing gaze trigger keys to the left and right, and also below and above the centre of the screen. Moreover, saccadic responses do not induce a near-far dimension (as it is the case for manual responses along the sagittal axis, or for up/down keys located below the screen), and they do not induce a left/right hand confound for the up/down responses, all of which can bias spatial associations (Chen et al, 2015;Hartmann, Gashaj, et al, 2014;Santens & Gevers, 2008;Wiemers et al, 2017;Zhou et al, 2019Zhou et al, , 2020. Thus, saccadic responses overcome critical issues that were observed in previous studies that used manual responses.…”
Section: 3mentioning
confidence: 95%
“…This study further established that the oculomotor system is a valid alternative to manual responses when exploring the link between space and serial order (Rinaldi et al, 2015). In this study, we used saccadic responses in order to avoid problems that are typically induced by manual responses along the vertical axis, such as the closefar dimension or the left-right hand association (e.g., Chen et al, 2015;Hartmann, Gashaj, et al, 2014;Wiemers et al, 2017;Zhou et al, 2020). Besides these rather technical aspects, eye movements might generally play a special role in exploring the spatial nature of thoughts (e.g., Hartmann, 2015;Loetscher et al, 2010;Mast & Kosslyn, 2002;Rinaldi et al, 2015).…”
Section: Implications For Future Researchmentioning
confidence: 99%